Cryptocurrency as a Digital Property in Indonesian Law Perspective - Bintarto, Muhammad Al Ikhwan (Universitas Muhammadiyah Yogyakarta, 2022)
Cryptocurrency is the result of technological developments. The first cryptocurrency is bitcoin, introduced by Satoshi Nakamoto as a decentralized digital currency with a safe haven. Then over time, some countries recognized cryptocurrency as property are Netherlands, China, and others. Indonesia has classified cryptocurrency as a commodity. This study will discuss the legal views of property in Indonesian law regarding cryptocurrency. This study analyzed cryptocurrencies according to the material elements in Indonesian law, considering the classification of cryptocurrencies as commodities in Indonesia. This research applied a normative method with a statutory approach through primary and secondary legal materials, analyzed by descriptive analysis. This research found several material aspects in KUH Perdata that could be fulfilled in cryptocurrency. Law No. 19 of 2016 concerning Information and Electronic Transactions article 1 paragraph 2 mentions that Electronic transactions are legal acts carried out using a computer, computer network, or other media.